2017
DOI: 10.3389/fcimb.2017.00329
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Plasmodium Hepatic Infection by Antiretroviral Compounds

Abstract: Recent WHO guidelines on control of human immunodeficiency virus (HIV) call for the widespread use of antiretroviral (AR) therapy (ART) for people living with HIV. Given the considerable overlap between infections by HIV and Plasmodium, the causative agent of malaria, it is important to understand the impact of AR compounds and ART regimens on infections by malaria parasites. We undertook a systematic approach to identify AR drugs and ART drug combinations with inhibitory activity against the obligatory hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…A recent investigation of the impact of ARVs on the liver stage of Plasmodium infection has shown that, consistent with what is observed for erythrocytic stages, the PIs LPV and RTV are potent inhibitors of the parasite's development in hepatic cells (Hobbs et al, 2009). A reduction in the in vivo Plasmodium yoelii liver burden by NNRTIs (Hobbs et al, 2012) and of the in vivo Plasmodium berghei liver burden by etravirine (ETV) (Machado et al, 2017) have also been reported.…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations
“…A recent investigation of the impact of ARVs on the liver stage of Plasmodium infection has shown that, consistent with what is observed for erythrocytic stages, the PIs LPV and RTV are potent inhibitors of the parasite's development in hepatic cells (Hobbs et al, 2009). A reduction in the in vivo Plasmodium yoelii liver burden by NNRTIs (Hobbs et al, 2012) and of the in vivo Plasmodium berghei liver burden by etravirine (ETV) (Machado et al, 2017) have also been reported.…”
Section: Introductionmentioning
confidence: 52%
“…Thus, infection with HIV might increase the severity of Plasmodium infection, while the HIV viral load has been shown to increase during a Plasmodium infection (Nyabadza et al, 2015;Kwenti, 2018). Numerous studies report the effect of HIV ARVs on the different stages of the Plasmodium life cycle (Parikh et al, 2005;Andrews et al, 2006;Lek-Uthai et al, 2008;Hobbs et al, 2009Hobbs et al, , 2012Hobbs et al, , 2013Peatey et al, 2010;Li et al, 2011;Nsanzabana and Rosenthal, 2011;Machado et al, 2017). However, little is known about how ARTs may impair the transmission and mosquito stages of Plasmodium parasites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The in vitro activity of harmicines against the hepatic stages of Plasmodium infection was evaluated by employing rodent P. berghei parasites and a human hepatoma cell line (Huh7), as previously described [ 25 , 26 ]. Each compound was assessed at 1 and 10 μM ( Figure 2 ), with harmine and DMSO serving as positive and negative controls, respectively.…”
Section: Resultsmentioning
confidence: 99%